ISOLASI GELATIN DARI KULIT KAKI AYAM BROILER DAN KARAKTERISASI GUGUS FUNGSINYA DENGAN SPEKTROFOTOMETRI FTIR - Puspawati, N. M.; Simpen, I N.; Sumerta Miwada, I N. (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 1 Januari 2012)
Gelatin is a biopolymer that can be obtained from partially hydrolysis of collagen present in skin, bone, and connective tissues of animals. The aim of the present work is to isolate and characterize gelatin obtained from chicken feet Broiler’s skin after curing with acid and base. Isolation of gelatin from skin of chicken feet Broiler was performed by water-bath extraction through type A (acid) and type B (base) processes. CH3COOH 1.5% (GA) was used for acid-curing, and NaOH 2.0% (GB) for base-curing processes with 2 days soaking time. Gelatin prepared from acid-curing (GA) gave yield 8.47%, protein content 82.59%, and 23.50%. While gelatin from alkali process (GB) gave yield 7.37%, protein content 79.75% %, and fat content 15.76%. FTIR spectra of GA and GB were very similar. Both GA and GB exhibited peaks at wavelength number for region of amide A, amide I, II, and III which a characteristic for gelatin functional groups. GB exhibited peaks at 1242 cm-1 with low intensity in the amide III region while GA did not. This result is associated with the loss of triple helix or denaturation of collagen to gelatin. Based on FTIR results it can be concluded that GA and GB obtained were true gelatins, although GA gave a better result.
Keywords: isolation, gelatin, FTIR analysis, collagen, skin of chicken feet Broiler